The Principles of Landscape Design in Making Compositions - Babakandov Otabek Nuritdinovich; Aliyeva Nasiba Xasan qizi (Genius Journals, 2022)
This article presents the principles of landscape design in making different compositions
Keywords: Landscape; contrast; rhythm